The Population Genetics of Alternaria tenuissima in Four Regions of China as Determined by Microsatellite Markers Obtained by Transcriptome Sequencing - Yang, Naibo; Ma, Guoping; Chen, Kenxi; Wu, Xuehong (Frontiers in Microbiology, 2018)
A total of 32,284 unigenes were obtained from the transcriptome of Alternaria tenuissima, a pathogenic fungus causing foliar disease in tomato, using next-generation sequencing (NGS) technology. In total, 24,670 unigenes were annotated using five databases, including NCBI non-redundant protein, Swiss-Prot, euKaryotic Orthologous Groups, Kyoto Encyclopedia of Genes and Genomes, and the Gene Ontology. A total of 1,140 simple sequence repeats were also identified for use as molecular markers. Sixteen of the simple sequence repeat loci were selected to study the population structure of A. tenuissima. A population genetic analysis of 191 A. tenuissima isolates, sampled from four geographic regions in China, indicated that A. tenuissima had a high level of genetic diversity, and that the selected simple sequence repeat markers could reliably capture the genetic variation. The null hypothesis of random mating was rejected for all four geographic regions in China. Isolation by distance was observed for the entire data set, but not within clusters, which is indicative of barriers to gene flow among geographic regions. The analyses of Bayesian and principal coordinates, however, did not separate four geographic regions into four separate genetic clusters. The different levels of historical migration rates suggest that isolation by distance did not represent a major biological obstacle to the spread of A. tenuissima. The potential epidemic spread of A. tenuissima in China may occur through the transport of plant products or other factors. The presented results provide a basis for a comprehensive understanding of the population genetics of A. tenuissima in China.